EMPOWERMENT OF KARANG TARUNA PATTAPPA VILLAGE THROUGH EXACT TRAINING AND TECHNOLOGY FOR PROCESSING SOLID SANDSTONE - Nur Asmiani; Alfian Nawir; Gerard Antonini Duma; La Ifa; Taufik Nur; Andi M. Tundru; Abudzar Adhary Yusra; Aura Cahya Kemala (LPPM Univ. Ibn Khaldun Bogor, 2026)
This community service activity (PkM) is carried out in Pattappa Village, Pujananting District, Barru Regency, South Sulawesi, with a focus on increasing the capacity of Karang Taruna in managing the potential of local natural resources in the form of solid sandstone. Pattappa Village has unique geological potential with high-quality solid sandstones; however, utilization is still limited to simple products and has not provided significant economic added value. Activity implementation methods include preparation stages (observation and pre-test), implementation stage (training through direct discussion and practice of sand processing), and evaluation stage (post-test and observation of practical results). A total of 40 participants participated in this activity, consisting of Karang Taruna managers, village apparatus, and residents, with a high level of participation. Pre-test and post-test analysis results showed significant improvements, with index values of 90.5% including the category of strongly agree. This confirms that Pkm activities are practical, as well as knowledge, skills, and community awareness of local potential. Increased capacity of village youth through Karang Taruna is expected to support the development of value-added craft products based on pejal sand, so they can become the village’s flagship product that supports sustainable economic growth.